PERANAN GURU SEBAGAI SUPERVISOR KELAS TERHADAP KELANCARAN PROSES BELAJAR MENGAJAR - Syafrawi, Syafrawi (Al-Ulum : Jurnal Penelitian dan Pemikiran Ke Islaman, 2019)
Efforts to improve the quality of education always require sustained conditions of high discipline in addition to requiring energy, costs and time to achieve the expected goals. Education lasts a lifetime, therefore education is a shared responsibility between the government, family and society. Of the three educational environments it is an integral part of achieving these objectives ranging from kindergartens to tertiary education both private and public. according to the term Indonesian is "People whose jobs (livelihood, profession) teach". While the words of supervision when viewed from etymology are from English, namely Supervition. The teaching and learning process is a process that contains a series of actions by teachers and students on the basis of reciprocal relationships that take place in educational situations to achieve certain goals. To achieve the goals in the teaching and learning process, the smooth running of the teaching and learning process must be fulfilled.